2019
DOI: 10.1039/c9ob01549c
|View full text |Cite
|
Sign up to set email alerts
|

The Mukaiyama type aldol reaction for the synthesis of trans-2,6-disubstituted tetrahydropyrans: synthesis of diospongin A and B

Abstract: The synthesis of 2,6-trans-disubstituted tetrahydropyrans following the Mukaiyama type aldol reaction through C–C bond formation demonstrates the practicality of this protocol in the total synthesis of diospongin A and B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Reaction of 214 with excess TBAF furnished 76 a via retro-Michael opening of pyran ring followed by an intramolecular oxy-Michael reaction and desilylation leading to a more thermodynamically stable cis isomer (Scheme 57). [129] Dongjoo Lee's research group (2021) reported a dehydrogenative cycloetherification of a hydroxyl alkene through 6endo cyclization, yielding a dihydropyran employing DDQ. This method was effectively applied in the synthesis of racemic (�)centrolobine.…”
Section: Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reaction of 214 with excess TBAF furnished 76 a via retro-Michael opening of pyran ring followed by an intramolecular oxy-Michael reaction and desilylation leading to a more thermodynamically stable cis isomer (Scheme 57). [129] Dongjoo Lee's research group (2021) reported a dehydrogenative cycloetherification of a hydroxyl alkene through 6endo cyclization, yielding a dihydropyran employing DDQ. This method was effectively applied in the synthesis of racemic (�)centrolobine.…”
Section: Other Methodsmentioning
confidence: 99%
“…Reaction of 214 with excess TBAF furnished 76 a via retro‐Michael opening of pyran ring followed by an intramolecular oxy‐Michael reaction and desilylation leading to a more thermodynamically stable cis isomer (Scheme 57). [129] …”
Section: Tetrahydropyran Diarylheptanoidsmentioning
confidence: 99%
“…Very recently, we reported the synthesis of 2,6-trans-disubstituted tetrahydropyrans with a keto functionality following a Mukaiyama-type aldol reaction of 1-phenyl-1triemthylsiloxyethylene with six membered cyclic hemiacetals in the presence of iodine. 6 To apply further the Mukaiyama-type aldol reaction and as a part of our ongoing research on the total synthesis of biologically active natural products containing pyran rings, 7 herein, we report an efficient and convergent synthesis of curvulone B in seven steps.…”
Section: Figure 1 Structures Of Curvulone a (1) And Curvulone B (2)mentioning
confidence: 99%
“…Tandem isomerization followed by a C-O and C-C bond formation protocol under Mukaiyama-type conditions was performed by treating 7 with trimethyl(vinyloxy)silane in the presence of a catalytic amount of molecular iodine in anhydrous CH2Cl2 at room temperature to furnish trans-2,6-disubstituted-3,4-dihydro-pyran 5 as the sole product in 81% yield. 6,9,10 Scheme 2 Synthesis of compound 5…”
Section: Scheme 1 Retrosynthetic Analysis Of Curvulone B (1)mentioning
confidence: 99%